Daniel C. Dennett Responds to Richard Sosi's review of Breaking the Spell - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "Daniel C. Dennett Responds to Richard Sosi's review of Breaking the Spell." Free Inquiry 27, no. 1 (2006): 59-63.